Digitalisasi Al-Qur'an dan Tafsir Sosial Media di Indonesia - Muhamad Fajar Mubarok; Muhamad Fanji Romdhoni (Jurnal Iman dan Spiritualitas, 2021)
Al-Qur'an and Tafsir in the digital era are closely related to current technological developments. Various information and data that used to be difficult to obtain, with the development of technology become very easy, including the Al-Qur'an and its interpretation. From the editorial, the author focuses this discussion on the question, "How is the digitization of the Qur'an and Tafsir in Indonesia?". The method used by the author is the qualitative method (library research) through the literature, namely books and other scientific works. The results of this research are: first, the sacredness of the Qur'an. Mushaf al-Qur'an which when touching it in ethics requires ablution, after becoming software it loses its sacredness. Second, the interpretation of social media. Anyone can interpret the Koran on social media, as a result the interpretation of the Koran on social media is blurred because not only people who have studied religion for decades interpret the Koran, but also people who are just learning religion on social media.